Resurrection of Oral Arsenic Trioxide for Treating Acute Promyelocytic Leukaemia: A Historical Account From Bedside to Bench to Bedside - Kumana, Cyrus R.; Mak, Raymond; Kwong, Yok-Lam; Gill, Harinder (Frontiers in Oncology, 2020)
Various forms of arsenic were used in China and elsewhere for over 5000 years. Following the initial success of intravenous arsenic trioxide (i.v. As2O3), we revived an oral formulation of pure As2O3 in 1998 for the treatment of acute promyelocytic leukaemia (APL). We were the first to produce a 1mg/ml oral-As2O3 solution and showed that it had comparable bioavailability to i.v. As2O3. Moreover, we also reported that intracellular arsenic concentrations were considerably higher than the corresponding plasma values. Our oral-As2O3 was patented internationally and registered in Hong Kong for the treatment of APL. Safety, tolerability and clinical efficacy was confirmed in long-term follow-up studies. We have extended the use of oral-As2O3 to frontline induction of newly diagnosed APL. With these findings, we are moving towards an era of completely oral and chemotherapy-free management of APL.